The role of UTAUT, DOI, perceived technology security and game elements in internet banking adoption. Issue 4 (21st September 2018) - Rahi, Samar; Abd. Ghani, Mazuri
Abstract : Purpose: The increasing innovation and urgent need of up-to-date and convenient information systems have gained high importance in financial sector. Several banks have deployed internet banking in order to reduce cost while improving customer services. Therefore, the growth of internet banking is limited and in many cases fallen short of expectations. The purpose of this paper is to develop an integrated model that combines technology, innovative and environmental factors altogether in order to understand customer's intention to adopt, and intention to recommend internet banking in social networks. Design/methodology/approach: In all, 398 valid responses were collected from customers of commercial banks, using convenience sampling approach. Data were analyzed using the structural equation modeling. Findings: The findings show that integrated model has good explanatory power (78.3 percent) to predict customer's intention to adopt internet banking. Findings also revealed that the interaction effect of gamification between user's intention to adopt and user's intention to recommend internet banking will be stronger when gamification effect is higher. Importance performance matrix analysis (IPMA) revealed that innovativeness and perceived technology security were the most important factors in order to determine user's intention with regard to adoption of internet banking. Practical implications: For policy-makers, it is suggested that they should focus on innovative characteristics and must ensure the possible environment for carrying out internet banking transaction. Advertising about new technology with adequate information may produce positive influence on user's intention. Enjoyable internet banking website with reward system will help to improve user's intention to adopt and intention to recommend internet banking with others, thus developers should introduce game features on internet banking website. Originality/value: This study provides basis for further refinement of individual technology acceptance models and enrich the e-commerce literature adding innovative and game elements in interne banking adoption context. Additionally, the proposed model makes an important contribution in emerging e-commerce literature especially in the context of innovative and gamified internet banking.